ЗАСТОСУВАННЯ КІНЕЗОТЕРАПІЇ ТА ТЕЙПУВАННЯ У КОМПЛЕКСНОМУ ВІДНОВЛЕННІ ДІТЕЙ 4-7 РОКІВ ЗІ СПАСТИЧНИМ ТЕТРАПАРЕЗОМ - Kozik, Nataliia Mykolaiivna; Tolok, Kateryna Vitaliivna (SWorld &D.A. Tsenov Academy of Economics, Svishtov,Bulgaria, 2022)
The article is devoted to substantiation and practical confirmation of the effectiveness of the use of a set of therapeutic exercises in combination with taping in the complex program of physical therapy of patients with spastic tetraparesis. The study experimentally confirmed the positive results of combining a set of exercises for the development of motor functionsand kinesiotaping of the neck, abdomen and back, which improved large motor functions, posture and reduced spasticity.
АPPLIKATION OF KINESIOTHERAPY AND TAPE IN COMPLEX RECOVERY OF 4-7 YEAR-OLD CHILDREN WITH SPASTIC TETRAPARESIS
Keywords: cerebral palsy in children, tetraparesis, complex physical therapy program, kinesiotaping, children aged 4-7.; дитячий церебральний параліч, тетрапарез, спастична геміплегія, комплексна програма фізичної терапії, реабілітація, діти 4-7 років